Pengaruh Konten Brand Awareness pada Instagram Harris Hotel & Convention Cibinong City Mall Bogor terhadap Minat Tamu Menginap - Trinandhi, Syafira Ramadanti; Dharmawan, Leonard (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study focuses on determining the extent to which brand awareness content on the Instagram account of Harris Hotel & Convention Cibinong City Mall Bogor can influence guest interest in staying. Through a quantitative approach, this study involved 100 respondents who were followers of the Instagram account. Data were collected through questionnaires and analyzed using simple linear regression to determine how much influence brand awareness content had on guest interest in staying. The results of the study showed a positive and significant influence of brand awareness content on guest interest in staying at Harris Hotel & Convention Cibinong City Mall Bogor. This is reflected in the regression coefficient value of 0.658 and a significance level of 0.000 (<0.05). In other words, the more effective the brand awareness content displayed through Instagram, the greater the guest interest in choosing Harris Hotel as a place to stay. This study provides recommendations for hotels to maximize their brand awareness content strategy on Instagram. Presenting creative, relevant, and interesting content according to audience preferences is an important key to increasing the attraction and interest of guests to stay.